POLICY EVALUATION OF CASHLESS PAYMENT SYSTEM IN PUBLIC TRANSPORTATION SERVICES OF “TRANS BANYUMAS” BUY THE SERVICE PROGRAM IN BANYUMAS REGENCY - APRIL KURNIAWAN; Aliefia Elfarizza; Alyani Ainun Nafis; Anisa Afri Inayah (Jurnal Ilmu Pemerintahan Widya Praja, 2025)
This study evaluates the cashless payment system policy in the Buy The Service program of the Ministry of Transportation of the Republic of Indonesia, focusing on the Trans Banyumas service in the Banyumas Regency. The digitization of payment systems in the transportation sector is expected to improve operational efficiency and transaction transparency and shift people's payment patterns from cash to cashless. However, implementing this policy still faces challenges, including technical constraints and user preferences for payment methods. This study employs a descriptive qualitative approach using William Dunn's evaluation theory and data collection methods through observation, interviews, and documentation. The results indicate that the cashless payment system has effectively enhanced transaction efficiency and transparency. However, there is a gap in payment methods, as most passengers prefer e-money cards over QRIS. This preference is influenced by limited internet access and the 90-minute integration fare policy, which only applies to e-money cards. Thus, it can be concluded that the cashless payment system policy in the public transportation service of the Buy The Service Trans Banyumas program has made a positive contribution but still requires optimization, particularly in equalizing the integration fare policy and improving payment infrastructure.